Plasma-Activated Municipal Wastewater (PAMW): Revolutionizing Municipal Wastewater into High-Value Liquid Fertilizer for Duckweed Cultivation through Air Plasma Treatment - Ungwiwatkul, Sunisa; Jaikua, Mathin; Prasertboonyai, Kanyarak; Thana, Phuthidhorn; Tamman, Arlee; Matra, Khanit (Applied Science and Engineering Progress, 2025)
This study investigates the potential of pin-to-water surface atmospheric pressure air plasma-activated municipal wastewater (PAMW), driven by solar energy, for cultivating duckweed (Lemna minor L.). By capitalizing on the essential macronutrients, especially phosphate, inherent in the wastewater, the research aims to create a cost-effective source of plant nutrients. The air plasma treatment not only efficiently purifies the wastewater but also yields vital nitrogen fertilizer, particularly nitrate and ammonium, at no extra cost. The optimal 1.00 cm discharge gap in a plasma-electrolysis reactor with three anode modules maximizes the reduction of the chemical oxygen demand (COD) in PAMW. The treatment significantly degrades contaminants, notably reducing COD values, with the longest treatment time (30 min) producing the highest nitrite, nitrate, ammonium and hydrogen peroxide content—87.00 ± 0.46 mg/L, 54.72 ± 0.66 mg/L, 6.62 ± 0.06 mg/L and 69.98 ± 0.66 mg/L, respectively. Under these optimal conditions, duckweed cultivation in PAMW exhibits substantial growth, increasing biomass by 6.4 times in 7 days. Crude protein rises from 12.52 % of dry weight (DW) to 33.06 % DW, carotenoid content increases from 1346.12 µg g–1 DW to 2816.11 µg g–1 DW, and total chlorophyll grows from 4.26 mg g–1 DW to 10.40 mg g–1 DW. The COD of PAMW significantly decreases from 138.67 mg/L to 48.00 mg/L. These findings propose a cohesive and cost-effective approach to the sustainable cultivation of duckweed and other plants using enhanced PAMW.